Running for the Future: Reproductive Futurity in Canadian Breast Cancer Survivorship Discourse - Pack, Rachael (Imaginations)

(untitled) (York University, 2020)
This article critically examines the proliferation of images of youthful breast-cancer survivors within Canadian Breast Cancer Foundation’s (CBCF) promotional materials, explicating how such images of survivorship are inextricably tied up with the (re)production of gender, sexual, temporal, and citizenship norms. Focusing specifically on the 2013 Run for the Future campaign, I trace how the figure of the prepubescent child and narratives of emerging (hetero)sexuality operate to project a vision of the future, which is marked by the inevitability of both breast cancer and fractured nuclear families. I consider how such imaginations of an unstable future are mobilized to promote participation in the Run for the Cure (the philanthropic event promoted by CBCF’s multimedia campaign). Drawing on insights from queer theory, I highlight how the youthful survivor subject is embedded within a discourse of reproductive futurity in which her nascent citizenship is inextricable from her projected motherhood and heterosexuality. I suggest that the campaign constructs breast cancer as a disease that threatens the integrity and continuance of the heterosexual, nuclear family, and thus constitutes an unavoidable risk that must be addressed by citizens in the name of the future. Ultimately, I argue that participation in the Run for the Cure is styled not as a strategy to protect girls and future women, but rather to safeguard an imagined, desired heterosexual future.